Найдите значение выражения: (a-3b)^2+9b(a-b) при a=-2,b=3.​

envoyfromhell envoyfromhell    3   30.01.2020 07:44    18

Ответы
Viktoria12311 Viktoria12311  11.10.2020 03:56

-14

Пошаговое объяснение:

(a-3b)^2+9b(a-b)=a^2-2a*3b+(3b)^2+9ab-9b^2=\\=a^2-6ab+9b^2+9ab-9b^2=a^2+3ab\\\\a=-2,\;b=3\\a^2+3ab=(-2)^2+3*(-2)*3=4-18=-14

ПОКАЗАТЬ ОТВЕТЫ
Alice111111111111111 Alice111111111111111  11.10.2020 03:56

-14

Пошаговое объяснение:

а^2-6аb+9ab-b^2

собираем подобные

а^2+3ab

-4+3*(-2)*3

-14

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика